2016
DOI: 10.1016/j.eurpsy.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and depression in women: A 7-year prospective cohort study. The APNA study

Abstract: In this 7-year prospective study in the APNA women population, depression emerged in 8.9%. Being underweight or obese (not overweight) at baseline is significantly associated with future onset of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…This was in contrast to most findings from Western studies, which have reported that clinical overweight or obesity is significantly associated with depression 31 32 33 34 . In addition, others have reported that both underweight and obesity are associated with depression, and a U-shaped relationship between depression and BMI has been described 35 36 . However, our findings are consistent with a previous study conducted in the Chinese elderly, which also demonstrated an inverse relationship between BMI and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast to most findings from Western studies, which have reported that clinical overweight or obesity is significantly associated with depression 31 32 33 34 . In addition, others have reported that both underweight and obesity are associated with depression, and a U-shaped relationship between depression and BMI has been described 35 36 . However, our findings are consistent with a previous study conducted in the Chinese elderly, which also demonstrated an inverse relationship between BMI and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Or are changes in weight related to changes in depressive symptoms in a curvilinear pattern, with individuals becoming underweight and overweight scoring worse? Based on previous studies showing that underweight as well as overweight are associated with increased depressive symptoms [ 16 , 17 ], we hypothesize that the greater the change to the extreme of BMI, the greater the risk of an increase in depressive symptoms. More specifically, factors associated with obesity such as poor body image, maladaptive eating behaviors or avoidance of physical activity might explain the relationship between obesity and depressive symptoms [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to maternal mental health symptoms and maternal nutritional status, our finding that there was no association between more severe symptoms and BMI also diverged from the existing literature. Studies from high-income countries found relations between depressive symptoms and BMI to resemble a U-shaped curve, where depressive symptoms are associated with both underweight and overweight in adults [54][55][56]. Among women in the perinatal period, one study found that women with normal pre-pregnancy BMI (compared to obese and underweight women) had signficantly lower risk of postpartum depression symptoms.…”
Section: Discussionmentioning
confidence: 99%